The routine utilization of dental care during pregnancy in eastern China and the key underlying factors: a Hangzhou City study. - Wei Sun; Jing Guo; Xiuyang Li; Yongqi Zhao; Hui Chen; Gang Wu (PLoS ONE, 2014)
OBJECTIVES: Oral diseases are associated with adverse pregnancy outcomes. The routine utilization of dental care (RUDC) during pregnancy is an effective way to improve pregnant women's oral health, and thus safeguard the health of their babies. As China has one fifth of the world's population, it is especially meaningful to encourage RUDC there. However, the status of RUDC in China and the key underlying factors are largely unknown. METHODS: This cross-sectional survey investigated the current status of RUDC during pregnancy and the key underlying factors in Hangzhou City, Zhejiang Province, eastern China. We collected participants' demographics, individual oral-hygiene behaviors, individual lifestyle, oral-health conditions and attitudes, and also their RUDC during pregnancy. Binary Logistic Regression Analysis was used to analyze the key underlying factors. RESULTS: Only 16.70% of the participants reported RUDC during pregnancy. The percentage of RUDC was significantly lower among pregnant women with the following characteristics: aged 30 or less, an annual household income under $8,000, brushing once a day or less, never flossing or rinsing the mouth, paying no attention to pregnancy-related oral-health knowledge, and being dissatisfied with one's individual dental hygiene behavior. CONCLUSIONS: RUDC during pregnancy is very low in eastern China and is greatly influenced not only by a woman's age, annual income, individual hygiene behavior, but also by her attention and attitudes to oral health. To improve this population's access to and use of dental care during pregnancy, appropriate programs and policies are urgently needed.